PENERAPAN MODEL PEMBELAJARAN BERBASIS KECERDASAN INTERAKSIONAL UNTUK MENINGKATKAN KOMPETENSI BERBAHASA ARAB SISWA - Widayat, Prabowo Adi; Munthe, Bermawy; Musthofa, Tulus (Arabi : Journal of Arabic Studies, 2021)
Arabic learning at Madrasah Aliyah specifically aims to equip students with Arabic language competencies to be able to participate in global communication. Therefore, a learning model and its supporting components are needed that can encourage the achievement of these competencies for each student after participating in Arabic language learning. The scope of this research includes: (a) the application of interactional intelligence-based learning models for students of class XI Religious Sciences at MAN 1 Bandar Lampung in the even semester of the 2017/2018 academic year, (b) the effectiveness of the learning model in improving students' Arabic competence. This study uses a true experimental design by focusing on pretest-posttest control group design activities for the experimental class (given treatment) and control (not given treatment). The result shows that the application of the interactional intelligence-based learning model is convenient and has a significant influence in improving students' Arabic competence.